Coding body language in sports: The nonverbal behavior coding system for soccer penalties - Furley, P.; Roth, A. (Journal of Sport & Exercise Psychology, 2021)
Nonverbal behavior (NVB) plays an important role in sports. However, it has been difficult to measure, as no coding schemes exist to objectively measure NVB in sports. Therefore, the authors adapted the Body Action and Posture Coding System to the context of soccer penalties, validated it, and initially used this system (Nonverbal Behavior Coding System for Soccer Penalties [NBCSP]) to explore NVB in penalties. Study 1 demonstrated that the NBCSP had good to excellent intercoder reliability regarding the occurrence and temporal precision of NVBs. It also showed that the coding system could differentiate certain postures and behaviors as a function of emotional valence (i.e., positive vs. negative emotional states). Study 2 identified differences in NVB for successful and missed shots in a sample of penalties (time spent looking toward the goal, toward the ground, right arm movement, and how upright the body posture was). The authors discuss the utility of the coding system for different sport contexts.